A controlled study of potential risk factors preceding exacerbation in multiple sclerosis. Issue 3 (September 1995) - Gasperini, C; Grasso, M G; Fiorelli, M; Millefiorini, E; Morino, S; Anzini, A; Colleluori, A; Salvetti, M; Buttinelli, C; Pozzilli, C
Abstract : A wide variety of potential risk factors for acute exacerbations in multiple sclerosis were evaluated in a one year case-control study. Eighty nine consecutive patients with clinically definite multiple sclerosis and relapsing remitting course presenting with a relapse between January and December 1992 were compared with patients matched for age, sex, and degree of disability, who did not experience clinical exacerbations during the same period. Only potential risk factors occurring in the three months preceding the interview were considered patients. Relapsing patients reported no significant increase in the frequency of any risk factor in the three month period before exacerbation compared with the control group. These results suggest that most relapses are not preceded by the conditions commonly considered as risk factors.